Establishing the Dark Matter Relic Density in an Era of Particle Decays - Maldonado-Salazar, C (Institute of Physics Publishing, 2019)
If the early universe is dominated by an energy density which evolves other than radiation-like the normal Hubble-temperature relation H T2 is broken and dark matter relic density calculations in this era can be significantly different. We first highlight that with a population of states φ sourcing an initial expansion rate of the form H T2+n/2, for n-4, during the period of appreciable φ decays the evolution transitions to H T4. The decays of φ imply a source of entropy production in the thermal bath which alters the Boltzmann equations and impacts the dark matter relic abundance. We show that the form of the initial expansion rate leaves a lasting imprint on relic densities established while H T4 since the value of the exponent n changes the temperature evolution of the thermal bath. In particular, a dark matter relic density set via freeze-in or non-thermal production is highly sensitive to the temperature dependance of the initial expansion rate. This work generalises earlier studies which assumed initial expansion rates due to matter or kination domination. © 2019 IOP Publishing Ltd and Sissa Medialab.